Analysis of clinical manifestations, course and results of treatment of acute pancreatitis in patients of an emergency surgical hospital - Andrey I. Chavga; Oleg V. Midlenko; Vladimir I. Midlenko; Viktor A. Besov; Vladimir Yu. Shchegolev (ZAO "Consilium Medicum", 2024)
Background. Over the past 10-15 years, there has been a clear trend towards improving the diagnosis and treatment of acute pancreatitis. However, even at the current stage of technology development, a number of difficulties arise in making an accurate diagnosis, in determining the volume and timing of surgical intervention, in organizing measures to prevent complications, treatment and further recovery of patients after acute pancreatitis. Aim. To analyze the structure of morbidity and treatment outcomes of patients with acute pancreatitis in an emergency surgical hospital. Materials and methods. We analyzed the structure of pathology and incidence of acute pancreatitis in patients of the 5th and 6th surgical departments. The sample consisted of 2033 patients diagnosed with acute pancreatitis. Of these, 973 people are patients of the 5th surgical department, 1060 people are patients of the 6th surgical department. The work used standard mathematical and statistical methods of data processing. Results. The results indicate that in the structure of surgical pathology, the predominant diagnoses are acute pancreatitis, unspecified, and other acute pancreatitis. At the same time, these are also those forms of the disease that are characterized by high mortality. On average, 1 patient takes 9-10 bed days, which indicates the high medical and social significance of these forms of pathology. All the data obtained confirm the fact that many patients require emergency surgical care, even at a stage when the diagnosis has not yet been definitively confirmed. As a rule, indications for emergency surgical intervention appear already at the first stages of diagnosis, according to the main ultrasound criteria. The mortality rate averages 3-4%. Conclusion. The data obtained are approximately comparable with data obtained by other authors. In general, the literature notes that among all patients with pancreatitis, the acute form of the disease predominates. However, in terms of mortality, the results we obtained were slightly lower compared to the results for the country as a whole.